Bioefficacy of Trichoderma species against important fungal pathogens causing post-harvest rot in sweet potato (Ipomoea batatas (L.) Lam): Bioefficacy of Trichoderma metabolites of sweetpotato - DANIA, Victor Ohileobo (Journal of the Bangladesh Agricultural University, 2019)
Tuber rot disease constitutes a serious threat to sweetpotato production worldwide, causing economic losses to farmers. This study evaluated an eco-friendly approach using four biological control agents, Trichoderma viride, T. harzianum, T. hamatum and T. pseudokoningii for the management of post-harvest tuber rot disease of sweetpotato. Field surveys for infected tuber samples were conducted four across major sweetpotato states in Nigeria. Rot severity in inoculated tubers was evaluated over a storage period of four months and Trichoderma species isolated from the rhizosphere were bioassayed for the production of metabolites to evaluate the mechanism of antibiotic production for the control of rot pathogens using Gas Chromatography-Mass Spectroscopy. A total of 24 metabolites were produced by the Trichoderma species and the abundances were species dependent. Trichoderma species significantly (p<0.05) inhibited rot in treated tubers at 4 months after storage. However, T. harzianum was most effective, reducing mycelia growth of the rot pathogens by 54.6-77.3% in vitro and 47.2-68.8% reduction of rot incidence in vivo. The efficacy of Trichoderma species used in this study recommends their use as alternative therapy to synthetic fungicides in the management of post-harvest rot in sweetpotato. <!--StartFragment --> J Bangladesh Agril Univ 17(4): 446–453, 2019